The role of environmental access to exercise opportunities in cardiovascular mortality: evidence from a nationwide study - Wang, Xiaowen; Gu, Yongshi; Wang, Ying; Qiu, Yuqing; Chen, Tianling; Hopke, Philip K.; Zhang, Kai; Lin, Shao; Qu, Yanji; Lin, Ziqiang; Deng, Xinlei; Sun, Jie; et al. (BMC medicine, 2025)
Background Environmental access to exercise opportunities plays a crucial role in determining the level of physical activity within a population. However, it is unclear how environmental factors contribute to disparities in physical activity and health outcomes. We explored the associations between county-level access to exercise opportunities and cardiovascular disease (CVD) mortality across US counties. Methods We conducted an ecological analysis using aggregated data from two primary sources: the County Health Rankings and Roadmaps data and CDC WONDER mortality data. We compared county-level age-adjusted CVD mortality across county-level quartiles of access to exercise opportunities and physical inactivity. Stratification was performed based on age, sex, race, and urbanization variables. The rate ratio (RR) for CVD mortality was also calculated using generalized linear models. Results We observed significant variations in CVD mortality across different levels of exercise opportunities access and physical inactivity, which was consistent across all demographic subgroups ( P < 0.001). Access to exercise opportunities was significantly associated with a reduced risk of CVD mortality (RR = 0.93 [0.91–0.95]), and the association was most pronounced for acute myocardial infarction (AMI) mortality (RR, 0.80 [0.76–0.85]). The county-level physical inactivity was significantly associated with an increased risk of CVD mortality (RR, 1.16 [1.14–1.17]), especially for ischemic heart disease (IHD) (RR, 1.35 [1.31–1.38]) and AMI (RR, 1.32 [1.25–1.38]). All demographic subgroups demonstrated similar benefits in reducing the risk of CVD by improving the county-level indicators of physical activity. Conclusions Counties have the potential to make significant environmental strides in improving the cardiovascular health of their populations by enhancing access to exercise opportunities in the context of urbanization.